The rs2296651 (S267F) variant on NTCP (SLC10A1) is inversely associated with chronic hepatitis B and progression to cirrhosis and hepatocellular carcinoma in patients with chronic hepatitis B. Issue 9 (7th December 2015) - Hu, Hui-Han; Liu, Jessica; Lin, Yu-Ling; Luo, Wun-Sheng; Chu, Yu-Ju; Chang, Chia-Lin; Jen, Chin-Lan; Lee, Mei-Hsuan; Lu, Sheng-Nan; Wang, Li-Yu; You, San-Lin; Yang, Hwai-I; et al.
Abstract : Objective: The sodium taurocholate co-transporting polypeptide (NTCP), encoded by SLC10A1, was recently identified as a receptor for HBV. We assessed the association of the p.Ser267Phe variant (rs2296651) with chronic hepatitis B (CHB) serostatus, cirrhosis and hepatocellular carcinoma (HCC) in patients with CHB. Design: The variant was genotyped in 3801 patients with CHB and 3801 matched hepatitis B surface antigen (HBsAg) seronegative individuals. ORs with 95% CIs for the variant's association with CHB, cirrhosis and HCC were estimated using logistic regression. Results: In patients with CHB, the S267F variant was observed in 515 (18.5%) controls, 40 (17.2%) cirrhosis only cases, 49 (13.2%) non-cirrhotic HCC cases, and 52 (12.7%) cirrhotic-HCC cases. After adjustment for known risk factors, S267F was significantly associated with decreased risk for cirrhosis (OR 0.65 (95% CI 0.49 to 0.86), p=0.002) and HCC (OR 0.55 (95% CI 0.42 to 0.72), p<0.001). This association persisted for non-cirrhotic and cirrhotic-HCC. Compared with patients with HBV DNA levels greater than 10 5 copies/mL who carried the GG genotype, patients who had undetectable HBV DNA and the GA or AA genotypes had a 25-fold decreased risk of developing HCC (OR 0.04 (95% CI 0.02 to 0.11), p<0.001). The AA genotype was also associated with HBsAg seronegativity (OR 0.13 (95% CI 0.05 to 0.34), p<0.001). Conclusions: The SLC10A1 (NTCP) S267F variant is independently associated with decreased risk of cirrhosis and HCC, and resistance to CHB infection. Together with serum HBV DNA levels, S267F may help to identify patients with CHB with very low risk of HCC.